Pengaruh Permainan Kasti Terhadap Kemampuan Motorik Kasar Bagi Anak Sekolah Dasar - Purwanda, Ervin; Dinangsit, Dinar; Sudirjo, Encep (Universitas Hamzanwadi, 2025)
The purpose of this study was to determine the effect of baseball games on gross motor skills of elementary school children and to determine how much influence baseball games have on the gross motor skills of elementary school children. This study uses a quantitative method with the type of experimental research that will use a one group pretest posttest design. The instrument used is a motor ability test instrument consisting of 4 test items, namely standing broad jump, shot put test, zigzag run, 50 meter sprint. The population of this study were fifth grade students of SDN Damit 1 Cicalengka consisting of 20 boys and 10 girls. The results of the paired Sample T-Teist showed a significant number between the pre-test value of 7.10 and the post-test value of 9.50 with a significance value of 0.024 < 0.05. The result of R squares is 0.314. The baseball game has a significant influence on students' physical fitness. This is evidenced by the sig value. (2-tailed) 0.000 <0.05, which means that there is an influence of the inscription game on children's motor skills. Based on the results of the determination test, the results show that the baseball game has a 31% influence on children's motor skills.